Application of Volatile Antifungal Plant Essential Oils for Controlling Pepper Fruit Anthracnose by Colletotrichum gloeosporioides - Hong, Jeum Kyu (Plant Pathol J, 2015)
Anthracnose caused by Colletotrichum gloeosporioides has been destructive during pepper fruit production in outdoor fields in Korea. In vitro antifungal activities of 15 different plant essential oils or its components were evaluated during conidial germination and mycelial growth of C. gloeosporioides. In vitro conidial germination was most drastically inhibited by vapour treatments with carvacrol, cinnamon oil, trans-cinnamaldehyde, citral, p-cymene and linalool. Inhibition of the mycelial growth by indirect vapour treatment with essential oils was also demonstrated compared with untreated control. Carvacrol, cinnamon oil, trans-cinnamaldehyde, citral and eugenol were among the most inhibitory plant essential oils by the indirect antifungal efficacies. Plant protection efficacies of the plant essential oils were demonstrated by reduced lesion diameter on the C. gloeosporioides-inoculated immature green pepper fruits compared to the inoculated control fruits without any plant essential oil treatment. In planta test showed that all plant essential oils tested in this study demonstrated plant protection efficacies against pepper fruit anthracnose with similar levels. Thus, application of different plant essential oils can be used for eco-friendly disease management of anthracnose during pepper fruit production.